Model Hybrid Flowshop 2 Stage with Johnson’s Rule Dispacthing to Minimize Makespan - Anwar, Asep; Damur Rochman, Didit; Rahmana, Arief (International Journal of Psychosocial Rehabilitation, 2020)
Hybrid Flowshop (HFS) is a development scheduling model of flowshop scheduling problems. Currently, PT. XX is a manufacturing company that produces MT (mono-twine) mesh products using the HFS production concept. The HFS process at PT XX is the Ringrope (Stage 1) and Netting (Stage 2) process. The ringrope process consists of 2 machines arranged in parallel, and then the results will be processed by Netting. The settlement method in this research is the optimization method by making a mathematical model by sorting using the Johnson method. The results of the study showed the sequence of processes on stage 1 and on stage 2 with makespan was 1354.51 hours.